Greece : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2003 Article IV Consultation highlights that the economic expansion that began in Greece in the mid-1990s has continued unabated, with some employment gains in 2002 for the first time in four years. GDP increased by 4 percent in 2002, well above the European Union (EU) average, but external imbalances remained large. High capacity utilization, EU transfers, and preparations for the 2004 Olympics underpinned investment. Divergent cyclical positions and relatively high labor cost increases kept inflation well above the euro area average. Consumer price inflation averaged close to 4 percent in 2002.